Spanish pre-university students’ use of English: CEA results from the University Entrance Examination - Díez Bedmar, María Belén (International Journal of English Studies, 2011)
In this paper an updated overview of the main errors that Spanish students make when writing the English exam in the University Entrance Examination is provided. To do so, a Computer-aided Error Analysis (CEA) (Dagneaux, Denness & Granger, 1998) was conducted on a representative sample of the students who took the exam in June 2008 in Jaén, and wrote a composition on the same topic. The use of the most widely-used error taxonomy, the Error Tagging Manual version 1.1. (Dagneaux, Denness, Granger & Meunier, 1996), and the analysis of the results by means of descriptive statistics foster the possibility to replicate this study and move forward in the description of the students’ written command in the foreign language at this stage. The comparison of the findings obtained in this study and those from previous (C)EAs on the English exam reveals that some common tendencies may be shown.